Destrancar-tudo: a dinâmica circular dos banhos de folhas no colégio Estadual Luiz Viana Filho - Diego Cruz Argolo (2024)
In this study, I present a discussion and reflection on the process of ethnic-racial (self)identification of 2nd year high school students at the Luiz Viana Filho State College (CELVF), in Candeias-Bahia, through the study of the culture of sacral and medicinal leaf bath rituals, in the light of decolonial studies and critical racial literacy. Including immersion in different ancestral spaces – Terreiros de Candomblé, Benzedeiras backyards, herbalists from street markets and other ancestral backyards - the aim was for the students and the teacher researcher to discuss and reflect on the silencing and curtailment of these cultural manifestations and on religious racism in the school environment. To this end, the methodology used was autoethnographic, since I am the researcher/researched who aims to understand myself through reflection and the socio-cultural context in which I am immersed. In addition, I use cartography, which allows the researcher to dynamically record the stages of his or her self formative journey and that of the students, while it is happening. The research data includes audiovisual and written records, through the participants' logbooks, during the interactions in what I have called Ancestral Moments, which together with the Vence-Demandas Sequences make up the educational product of this study. Project pedagogy was used as a methodological strategy that made it possible to bring together the culture of using sacral and medicinal leaf baths with the socio-cultural context of the participants and, therefore, of that community. As a result, the students had the opportunity to identify and reflect on the various racisms/Kizilas present in the school environment.